Daniel X : Armageddon - James Patterson; Chris Grabenstein (Daniel X series bk, 2012)
Daniel faces dastardly Number Two, who has slowly been amassing an underground army of aliens to help him enslave Earth's population in preparation for the arrival of Number One, the most powerful alien in the universe and Daniel's arch-nemesis.